Petroleum generation and migration in the southern Tyumen region, Western Siberia Basin, Russia. (February 2021) - Goncharov, I.V.; Samoilenko, V.V.; van Graas, G.W.; Trushkov, P.V.; Oblasov, N.V.; Fadeeva, S.V.; Veklich, M.A.; Kashapov, R.S.; Sidorov, D.A.
Highlights: The Bazhenov Formation is the best petroleum source rock in southern Tyumen. Most reservoired petroleum has been generated from Bazhenov rocks. The main petroleum kitchen is located in the northeastern part of the region. Migration distances are up to 200 km for petroleum in Mid-Jurassic reservoirs. Abstract: A suite of geochemical studies on core and petroleum samples from the south of the Tyumen region (Western Siberia Basin, Russia) has been performed. Pyrolysis data from rock samples of Lower Cretaceous and Jurassic sediments establish the presence of at least four potential source rock intervals in the study area. Of these, the Upper Jurassic Bazhenov interval hosting marine organic matter has the greatest potential for oil and gas generation. The other identified source intervals are of lower quality and do not have a potential for generating significant amounts of liquid petroleum due to the terrestrial nature of the organic matter. A detailed study of petroleum and source rock extract data confirms that the Bazhenov source interval is the main source of all reservoired petroleum found in the region. Lower Cretaceous petroleum deposits are found at distances up to 100 km from the mapped Bazhenov kitchen areas. Petroleum deposits in Upper Jurassic reservoirs have been generated in local kitchens or have migrated over short distances only (10–20 km). The largest regional spread is seen in Bazhenov-generated petroleum in Middle Jurassic Tyumen reservoirs, which are found in deposits along migration routes from the kitchen areas towards the south and which can reach up to 150–200 km.